Representation of Modern Society in the Lyrics of "Berani Bersuara" by Laleilmanino and JKT48: A Study of Pop Mucis from the Cultural Studies Approach - RA Marizka Andyanita; Mellin Intan Sari; Darra Ananda (Communications, 2024)
This study examines the collaboration between Laleilmanino and JKT48 in the song "Berani Bersuara," which was released on May 27, 2022, as part of a digital literacy campaign by the Ministry of Communication and Information Technology (Kemenkominfo) and the National Digital Literacy Movement (GNLD) Siberkreasi. The song aims to educate young people about communication ethics on social media. In the context of globalization and technological development, cyberculture and social media have become integral parts of social and political interaction, allowing for widespread dissemination of information and expression, while also presenting challenges such as hoaxes and unethical behavior. Using Wilhelm Dilthey's hermeneutic approach and cultural studies, this research analyzes how the lyrics of "Berani Bersuara" represent social critique against the unwise use of social media. Secondary data from various sources were used to support this analysis. The findings indicate that the song advocates for wise and responsible communication in the digital world, aligning with the government's digital literacy program. The song also serves as a medium to convey social criticism, encouraging awareness and positive changes in social media users' behavior. This study affirms that pop music can be an effective tool for conveying social messages and supporting digital literacy campaigns, demonstrating the power of pop culture in influencing the views and behavior of young people in the modern era. Keywords: Cultural Studies, Hermeneutics, Digital literacy, Communication ethics, Cyberculture, Social critique.